Influence of culture medium and age of bovine blastocysts in established colonies of embryonic stem cells - Guastali, Midyan Daroz [UNESP]; Monteiro, Bianca Andriolo [UNESP]; Maziero, Rosiara Rasária D. [UNESP]; Paschoal, Daniela Martins [UNESP]; Sudano, Mateus José [UNESP]; Rascado, Tatiana da Silva [UNESP]; Lima Neto, João Ferreira [UNESP]; Vergara, Luis Eduardo [UNESP]; Crocomo, Letícia Ferrari [UNESP]; Maserati, Marc; Landim-Alvarenga, Fernanda da Cruz Landim [UNESP] (My University, 2015)
The objective of this study was to evaluate the potential of bovine IVF blastocysts at different stages of embryonic development in establishing ESC-like. Furthermore, blastocysts cultured in medium containing (10%) and (2.5%) fetal calf serum (FCS) were compared to determine if the serum concentration during in vitro culture alters the blastocyst's potential to establish ESC-like culture. It was observed that only ICM's from expanded blastocysts adhered to the monolayer (n=160) independent of the concentration of serum used during IVF culture. There were no observable differences in potential to establish ESC-like in embryos cultured with 2,5% or 10% FCS . The bFGF didn´t seems to be required for maintenance of bovine ESC-like regardless of culture conditions. Blastocysts and colonies in primary culture and after the first passage were positive for Oct4, Nanog, SSEA-3 and TRA-1-81. Expanded blastocysts gave rise to ESC-like colonies, and the addition of LIF was sufficient to maintain cells undifferentiated in culture.
Keywords: Embryonic stem cells; Bovine; Blastocyst; Fetal calf serum; LIF